The Relationship Between College Teachers’ Frustration Tolerance and Academic Performance - Shi, Song; Zhang, Zizai; Wang, Ying; Yue, Huilan; Wang, Zede; Qian, Songling (Frontiers in Psychology, 2021)
The purpose of this study was twofold: to validate the College Teachers’ Academic Frustration Tolerance (CTAFT) Questionnaire and the College Teachers’ Academic Performance (CTAP) Questionnaire, and to explore the relationship between frustration tolerance and academic performance among college teachers. A total of 25 experts were recruited to modify and validate both questionnaires, and the results showed that the questionnaires had good content validity. Exploratory factor analysis provided further evidence supporting the reliability of the CTAFT and the CTAP, suggesting that the instruments are reliable and valid. Confirmatory factor analysis showed that frustration tolerance affected academic performance, which could best be modelled in the three dimensions of Affect (AF), Preferred Difficulties (PD) and Action (AC). A total of 450 college teachers from each faculty of both universities were then recruited to explore the significant positive correlation between academic frustration tolerance and academic performance. The results from the structural equation model suggested that AC and PD combined significantly predicted academic performance. To our knowledge, this is the first study to explore the relationship between college teachers’ academic frustration tolerance and academic performance in China.